Study of Short-Term Abnormal Returns of Intial Public Offerings in Asean Stock Exchanges - Chen, Yao (2014)
In ASEAN, the optimistic estimation of the economic condition reflects the potential market of the stock exchange. Since primary market is one of the key parts of capital market that deals with Initial Public Offering (IPO), it becomes an interesting topic to develop this study regarding to the factors influence IPO Performance in ASEAN. Malaysia (BM), Thailand (SET), Indonesia (IDX), Singapore (SGX), Vietnam (HOSE) and Philippines (PSE) stock exchanges will be focused. However, Laos’ stock exchange (LSX) and Cambodia stock exchange (CSK) have some limitation to provide the relevant information. The time period of this study refers to the IPO in 2013 and investigates their performances. So the objective of this research is to investigate the factors that affect IPO Performance in ASEAN. The limitation and recommendation also will be made also. Furthermore, the Multiple Linear Regression analysis will be applied as the essential analysis technique.